2016
DOI: 10.5665/sleep.6236
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Rapid Eye Movement and Nonrapid Eye Movement Sleep without Total Sleep Loss Impairs Hippocampus-Dependent Fear Memory Consolidation

Abstract: Study Objectives: Sleep is important for consolidation of hippocampus-dependent memories. It is hypothesized that the temporal sequence of nonrapid eye movement (NREM) sleep and rapid eye movement (REM) sleep is critical for the weakening of nonadaptive memories and the subsequent transfer of memories temporarily stored in the hippocampus to more permanent memories in the neocortex. A great body of evidence supporting this hypothesis relies on behavioral, pharmacological, neural, and/or genetic manipulations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…51 Reduced NREM sleep and altered REM bout patterns in Grm7 −/− mice suggest abnormal sleep fragmentation, which has been specifically linked with deficits in contextual fear consolidation. 52 We did not observe any significant changes in qEEG spectra in Grm7 −/− mice relative to their littermates when left undisturbed in their home cage. This is consistent with a previous publication that reported no differences in baseline qEEG but found increased hippocampal theta power in Grm7 −/− mice during a working memory task.…”
Section: Discussionmentioning
confidence: 49%
“…51 Reduced NREM sleep and altered REM bout patterns in Grm7 −/− mice suggest abnormal sleep fragmentation, which has been specifically linked with deficits in contextual fear consolidation. 52 We did not observe any significant changes in qEEG spectra in Grm7 −/− mice relative to their littermates when left undisturbed in their home cage. This is consistent with a previous publication that reported no differences in baseline qEEG but found increased hippocampal theta power in Grm7 −/− mice during a working memory task.…”
Section: Discussionmentioning
confidence: 49%
“…Complex attention and working memory could change following one night without sleep [28]. Interestingly, cognitive decline in both cases is closely related to the hippocampus [29, 30]. TFC is a widely used method to assess learning and memory function in rodents [31].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study found that circadian-desynchronized rats, which exhibit fragmentation of REM and NREM sleep within nonfragmented sleep bouts, demonstrated impaired long-term memory on a fear-conditioning task. Further, this impairment in memory consolidation correlated with posttraining fragmentation of NREM and REM sleep (Lee et al, in press). Converging evidence has been found in humans.…”
Section: Introductionmentioning
confidence: 99%